Microfluidics: New Frontiers - Fernández Rivas, D. (Revista Cubana de Física; Vol 28 No 1 (2011), 2011)
Microfluidics has opened new frontiers due to the control abilities and new applications at minute dimensions. This work is dedicated mainly to highlight several applications and devices used up to date. The focus is set on those applications of probable interest to Cuba, which means, those related with Life Sciences; Medicine, Biotechnology, Genomics, etc.